DESIGN OF INTERNAL CONTROL SYSTEM, ACCOUNTING RECORDS, AND FINANCIAL REPORTING IN NAKAYAMA - Sukiantono Tang; Shandy Shandy (ConCEPt - Conference on Community Engagement Project, 2022)
This community service activity aims to create a useful accounting record system using the Microsoft Access application. This accounting record system will be implemented in an electronic goods trading business called Nakayama which has been established since 1994. Based on the information obtained, Nakayama is still recording all transactions that occur into his own record book manually and does not yet have an adequate accounting recording system. The method of this activity includes observation, interviews, and accounting system design using MS Access. The end result of this community service activities is a well-designed accounting system that helped the owner in making financial decisions for the future, which includes but not limited to generating financial statements, stock records, sales records, and purchase records.